METODE LIVING TAFSIR ATAS AYAT-AYAT NAFKAH DALAM KONTEKS EKONOMI RUMAH TANGGA MODERN - Wirda Garizahaq (SINERGI : Jurnal Riset Ilmiah, 2026)
ABSTRACT The "living interpretation" method, or living interpretation of the verses on livelihood in the context of modern household economics, involves understanding that the responsibility for livelihood no longer rests solely with the husband, but can also involve the wife, and the concept of ability (financial capacity) becomes a determinant of the level of livelihood. This interpretation considers gender equality, where women have equal rights to work and contribute to the family, as well as flexibility in meeting household needs in a manner that is in accordance with Islamic law and modern conditions. This paper examines the interpretation of Qur'anic verses relating to the obligation to provide for working women, focusing on Surah An-Nisa: 32 and 34. In Islamic tradition, the obligation to provide for is generally borne by men, but with the increasing participation of women in the workforce, questions arise regarding the relevance of this rule in the modern era. Through historical, anthropological, and sociological approaches, this study explores the context in which the verses were revealed, the social dynamics during the Prophet's time, and the changing roles of women in various societies throughout the Islamic world. The results of this study indicate that the division of responsibilities for providing for is dynamic and can be adapted to suit the times, as long as it does not violate the basic principles of justice in Islam. A more inclusive and contextual understanding of these verses is expected to provide relevant solutions to the issue of working women and the obligation to provide for the family. ABSTRAK Metode "living tafsir" atau penafsiran hidup atas ayat-ayat nafkah dalam konteks ekonomi rumah tangga modern melibatkan pemahaman bahwa tanggung jawab nafkah tidak lagi hanya pada suami, melainkan dapat juga melibatkan istri, dan konsep kemampuan (kemampuan finansial) menjadi penentu tingkat nafkah. Penafsiran ini mempertimbangkan kesetaraan gender, di mana perempuan memiliki hak yang sama untuk bekerja dan berkontribusi pada keluarga, serta fleksibilitas dalam memenuhi kebutuhan rumah tangga dengan cara yang sesuai syariat dan kondisi modern. Makalah ini mengkaji tafsir ayat-ayat Al-Qur'an yang berkaitan dengan kewajiban nafkah bagi perempuan yang bekerja, dengan fokus pada QS. An-Nisa: 32 dan 34. Dalam tradisi Islam, kewajiban nafkah umumnya dibebankan kepada laki-laki, namun dengan semakin meningkatnya partisipasi perempuan dalam dunia kerja, muncul pertanyaan mengenai relevansi aturan tersebut di era modern. Melalui pendekatan historis, antropologis, dan sosiologis, penelitian ini menelusuri konteks asal turunnya ayat, dinamika sosial pada masa Nabi, serta perubahan peran perempuan dalam berbagai masyarakat di dunia Islam. Hasil kajian ini menunjukkan bahwa pembagian tanggung jawab nafkah bersifat dinamis dan dapat diadaptasi sesuai dengan perkembangan zaman, selama tidak melanggar prinsip-prinsip dasar keadilan dalam Islam. Pemahaman yang lebih inklusif dan kontekstual terhadap ayat-ayat ini diharapkan dapat memberikan solusi yang relevan terhadap isu perempuan bekerja dan kewajiban nafkah dalam keluarga